HUBUNGAN PAPARAN DEBU KAYU DI LINGKUNGAN KERJA TERHADAP GANGGUAN FUNGSI PARU PADA PEKERJA DI PT. ARUMBAI KASEMBADAN, BANYUMAS - Rr Sarah Fadhilah Nafisa; Tri Joko; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2016)
One of the negative impact of wood industries was the emergence of air pollution such as sawdust particles originating from the processing of raw materials that could potentially lead to various health problems for workers especially lung function impairment.The purpose of this study was to determine the correlation of dust exposure in the work environment with impaired lung function on workers at PT. Arumbai Kasembadan Banyumas. This study was an observational research using cross sectional approach. The populations in this study are male workers of PT. Arumbai Kasembadan Banyumas division of production with a total of 54 people then 35 people were taken as samples based on the inclusion criteria. Data analysis using fisher exact test with a significant level of 95%. The results showed levels of sawdust at the sawmill was 0.135 mg/m3, wood working1 was 16,987 mg/m3 and wood working2 was 12,203 mg/m3. The results of lung function checkup on 35 workers shows that the majority of workers with impaired pulmonary function was as much as 30 workers. Fisher exact test result showed there is correlation between work period (p value = 0.026, 95% CI = 0.831 to 4.170), the use of PPE (p value = 0.049, 95% CI = 1.037 to 1.776), and the levels of dust (p value = 0.044, 95% CI = 0.849 to 3.112) with impaired pulmonary function of workers, while the time length of exposure variable showed there is no significant correlation between the time length of exposure with impaired lung function of workers (p value 1,000, 95% CI = 0,145-6,907). From the observed variables it was shown that work period, the use of PPE, and the total dust level were a factor which affects pulmonary function impairment to the workers. Therefore it is necessary to increase the efforts to control the total dust level in the wood working area and monitoring the use of masks regularly.